Applying music-and-movement to promote agency development in music education: a case study in a special school. Issue 1 (8th March 2020) - Sutela, Katja; Juntunen, Marja-Leena; Ojala, Juha
Abstract: In this article, we describe the agency development in one student with special needs through Dalcroze-based music-and-movement activities. The case study was conducted in the context of classroom music education in a special school. The data were produced via a teaching experiment (from August 2015 to March 2016), in which a group ( n = 13) of 15- to 16-year-old students participated in added lessons (one lesson per week) provided by the first author. The lessons included a variety of Dalcroze-based activities, such as singing with movement, quick reaction and follow exercises, movement improvisation, body percussion exercises, dances, and relaxation exercises. The data consist of video-recordings of the lessons, a research diary, and interviews with teachers, teaching assistants, a therapist, and a specialist of special education. During the teaching experiment, the case student's agency developed from being a passive outsider to being an active participant and leader. The change in agency was noticed also outside the classroom. The study suggests that using music-and-movement in a music classroom offers possibilities for nonverbal embodied interaction and thereby opportunities for the development of students' agency and autonomy foremost by developing their body and social skills. On a more general level, the article contributes to developing such music education theory and practice that acknowledges the significance of experience in learning music and in embodied interaction, where individuals interact and make sense of the world through nonverbal communication. In addition, this study highlights the strength of such education in supporting the development of the whole human being.